The collapse of the midnight ionosphere and behavior of meridional neutral winds at Townsville over a full solar cycle. Issue 11 (10th November 2015) - Dandenault, P. B.; Richards, P. G.
Abstract: This paper investigates the causes of the sudden descent (midnight collapse) of the ionosphere at Townsville, Australia, during the equinox periods of years between 1970 and 1980. The collapse of hm F 2 at midnight is found to occur on 89% of the 330 equinox nights that are investigated, and the mean magnitude of the midnight collapse is 84 km in the March equinox periods and 99 km in the September equinox periods. Observations of hm F 2 are used to determine equivalent meridional neutral winds using a first principles physics model. Harmonic analysis of these derived winds reveals the existence of significant diurnal (24 h), semidiurnal (12 h), and terdiurnal (8 h) tidal components. The contribution of wind harmonics to the midnight collapse is determined by band‐pass filtering the winds to only allow certain tides and then modeling their effect on hm F 2 near midnight. The results indicate that the diurnal, semidiurnal, and terdiurnal components of the meridional neutral wind all play a significant role at various times, but the effect of the 6 h wind component is minimal. The spectral analysis also reveals that the terdiurnal wind component becomes dominant during solar maximum. Electric fields do not appear to be responsible for the midnight hm F 2 collapse because it is seldom seen at the near‐conjugate station of Akita, Japan. Key Points: Midnight collapse of hm F 2 is regular feature of the ionosphere at Townsville Diurnal, semidiurnal, and terdiurnal tides are drivers of the midnight collapse Terdiurnal tide is dominant during solar maximum